2021
DOI: 10.3389/fspor.2021.720488
|View full text |Cite
|
Sign up to set email alerts
|

No Fans–No Pressure: Referees in Professional Football During the COVID-19 Pandemic

Abstract: Due to the COVID-19 pandemic, European elite football (a.k.a. soccer) leagues played the remaining season 2019/20 without or strongly limited attendance of supporters (i.e., “ghost games”). From a sport psychological perspective this situation poses a unique opportunity to investigate the crowd's influence on referee decisions and the associated effect of “home advantage.” A total of 1286 matches–played in the top leagues of Spain, England, Germany, Italy, Russia, Turkey, Austria and the Czech Republic–were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 39 publications
2
38
0
1
Order By: Relevance
“…This observation was further confirmed in a systematic literature review by Leitner et al (2022) , who identified 26 studies that analyzed the last portion of the 2019–20 season, when all matches were played behind closed doors. Out of these 26 studies, only six did not observe a significant and consistent overall decrease of the home advantage and referee bias in the considered leagues ( Almeida & Werlayne, 2021 ; Benz & Lopez, 2021 ; Krawczyk & Strawinski, 2020 ; Matos et al, 2021 ; Ramchandani & Millar, 2021 ; Wunderlich et al, 2021 ), while the other 20 ones did observe a significant decrease of these phenomena ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Cross & Uhrig, 2020 ; Cueva, 2020 ; Dilger & Vischer, 2020 ; Endrich & Gesche, 2020 ; Ferraresi & Gucciardi, 2020 , 2021 ; Fischer & Haucap, 2020 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Konaka, 2021 ; Leitner & Richlan, 2021a ; Link & Anzer, 2021 ; McCarrick et al, 2021 ; Rovetta & Abate, 2021 ; Santana, Bettega & Dellagrana, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ; Tilp & Thaller, 2020 ). Considering exclusively the peer-reviewed, multi-leagues studies, they found that nine out of 13 studies observed such a decrease ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Ferraresi & Gucciardi, 2021 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Leitner & Richlan, 2021a ; McCarrick et al, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ).…”
Section: Introductionmentioning
confidence: 89%
“…This observation was further confirmed in a systematic literature review by Leitner et al (2022) , who identified 26 studies that analyzed the last portion of the 2019–20 season, when all matches were played behind closed doors. Out of these 26 studies, only six did not observe a significant and consistent overall decrease of the home advantage and referee bias in the considered leagues ( Almeida & Werlayne, 2021 ; Benz & Lopez, 2021 ; Krawczyk & Strawinski, 2020 ; Matos et al, 2021 ; Ramchandani & Millar, 2021 ; Wunderlich et al, 2021 ), while the other 20 ones did observe a significant decrease of these phenomena ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Cross & Uhrig, 2020 ; Cueva, 2020 ; Dilger & Vischer, 2020 ; Endrich & Gesche, 2020 ; Ferraresi & Gucciardi, 2020 , 2021 ; Fischer & Haucap, 2020 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Konaka, 2021 ; Leitner & Richlan, 2021a ; Link & Anzer, 2021 ; McCarrick et al, 2021 ; Rovetta & Abate, 2021 ; Santana, Bettega & Dellagrana, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ; Tilp & Thaller, 2020 ). Considering exclusively the peer-reviewed, multi-leagues studies, they found that nine out of 13 studies observed such a decrease ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Ferraresi & Gucciardi, 2021 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Leitner & Richlan, 2021a ; McCarrick et al, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ).…”
Section: Introductionmentioning
confidence: 89%
“…Besides qualitative interviews and self-report questionnaires, a promising approach was recently put forward by Leitner and Richlan ( 2021b ). Their “Analysis System for Emotional Behavior in Football “ (ASEB-F) is a video-based categorical analysis system of nonverbal behavior during football matches.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to economic issues, such as the viability of clubs without spectator revenues, the changed stadium atmosphere is particularly striking. Early in the pandemic, there was anecdotal evidence that the behavior of players changed, e.g., toward referees, and recent studies indicate that the missing crowd indeed has an impact on the (nonverbal) behavior of players, staff and referees (Leitner and Richlan 2021b ). Since games without spectators were played in almost all European leagues from mid-2020 at the latest, the situation can be compared to a natural experiment.…”
Section: Discussionmentioning
confidence: 99%
“…These focus on the degree of deviation from the winning percentage of 50% (Matos et al, 2020). Researchers have highlighted that HA is consistently seen in regular season football league matches (Almeida and Leite, 2021;Leitner and Richlan, 2021). Courneya and Carron (1992) have cited four major game location factors thought to affect the degree of HA: (1) learning/familiarity factors; (2) rule factors; (3) travel factors; (4) crowd factors.…”
Section: Introductionmentioning
confidence: 99%
“…Crowd factors relate to crowd density affecting the mental state of the home team, causing changes in the players' actions/behaviors and performances and bringing about HA consequently (Agnew and Carron, 1994). Other than exerting a direct influence on the players, crowd factors are perceived to influence the referees' decisions (Leitner and Richlan, 2021;Wunderlich et al, 2021). In both cases, the anticipated processes are the crowd's behaviors of cheering and supporting the home team and/or booing the away team, which creates an advantageous environment for the home team and the contrary for the away team.…”
Section: Introductionmentioning
confidence: 99%